2020
DOI: 10.1371/journal.pone.0240086
|View full text |Cite
|
Sign up to set email alerts
|

Care of peripheral intravenous catheters in three hospitals in Spain: Mapping clinical outcomes and implementation of clinical practice guidelines

Abstract: Background Peripheral intravenous catheters (PIVCs) are the most widely used invasive devices worldwide. Up to 42% of PIVCs are prematurely removed during intravenous therapy due to failure. To date, there have been few systematic attempts in European hospitals to measure adherence to recommendations to mitigate PIVC failures. Aim To analyse the clinical outcomes from clinical practice guideline recommendations for PIVC care on different hospital types and environments. Methods We conducted an observational st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
3
9
0
1
Order By: Relevance
“…However, participants acknowledged that they did not engage in patient education, arguably the initial requirement for patient implication in care. The consequences of such lack of engagement are not surprising, as seen in other studies reported by our group where we identi ed that 50% of patients did not know anything about the catheter they carried [19]. These ndings are concerning in themselves, but also highlight the missed opportunities to embed patient education about multiple related safety areas such as infection prevention and control, hand hygiene, and vascular catheter care, where patients could have a crucial role [34].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, participants acknowledged that they did not engage in patient education, arguably the initial requirement for patient implication in care. The consequences of such lack of engagement are not surprising, as seen in other studies reported by our group where we identi ed that 50% of patients did not know anything about the catheter they carried [19]. These ndings are concerning in themselves, but also highlight the missed opportunities to embed patient education about multiple related safety areas such as infection prevention and control, hand hygiene, and vascular catheter care, where patients could have a crucial role [34].…”
Section: Discussionsupporting
confidence: 65%
“…However, implementing and adopting recommendations within CPGs can be protracted [21] due to clinician perceptions [22], the volume and quality of the evidence [23], and even di culties to integrate the mandates of different CPGs [17]. Speci cally, previous ndings from our group suggest that the decisionmaking of nurses was suboptimal regarding the adoption of CPG recommendations for preventing infectious complications and failure related to PIVC, highlighting behavioural and organisational differences between hospital environments and services [19]. Further exploring individual motivations, barriers and facilitators within organisations would contribute towards understanding the contextual elements that underpin decision-making around PIVC care [24,25].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…), and airborne pathogens, such as tuberculosis, being highly presented in the daily day of healthcare workers [3,4]. These workers are at risk of being exposed to diverse pathogens, from mortal (i.e., Ebola) to highly contagious viruses (i.e., Sars-covid-19) via material or surfaces and corporal fluids [5,6]. This threat among healthcare workers continues to be presented and has economical and health repercussions in the healthcare systems and the workers' physical and mental health [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These workers are at risk of being exposed to diverse pathogens, from mortal (i.e., Ebola) to highly contagious viruses (i.e., Sars-covid-19) via material or surfaces and corporal fluids [5,6]. This threat among healthcare workers continues to be presented and has economical and health repercussions in the healthcare systems and the workers' physical and mental health [5,6]. In order to decrease this hazard, serval educational programs have been created and implemented to raise awareness among healthcare workers regarding risk and prevention, including hand washing or disposal in specific resistant containers [7].…”
Section: Introductionmentioning
confidence: 99%